2010
DOI: 10.1007/s11199-010-9882-3
|View full text |Cite
|
Sign up to set email alerts
|

Why Doesn’t He Just Leave Me Alone? Persistent Pursuit: A Critical Review of Theories and Evidence

Abstract: An integrative review of three theories that explain why some individuals engage in persistent pursuit-coercive control theory, relational goal pursuit, and attachment theoryis presented. The meta-analytic evidence pointing to persistent pursuit as a gendered behavior is reviewed, and coercive control theory is used to explain gender differences. The strong conceptual and empirical overlap between coercive control as a form of intimate partner violence and persistent pursuit is examined. It is suggested that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 53 publications
3
85
2
Order By: Relevance
“…Generally speaking, stalking perpetration and victimization in current dating relationships appears to be a gender neutral problem. This is in contrast to research that has demonstrated women are more likely to be victimized by former relationship partners in dating relationships (Davis et al 2012). Thus, although women may be more likely to become stalking victims after relationship termination, our preliminary research suggests that both men and women are equally likely to be victims during intact relationships.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Generally speaking, stalking perpetration and victimization in current dating relationships appears to be a gender neutral problem. This is in contrast to research that has demonstrated women are more likely to be victimized by former relationship partners in dating relationships (Davis et al 2012). Thus, although women may be more likely to become stalking victims after relationship termination, our preliminary research suggests that both men and women are equally likely to be victims during intact relationships.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be due to the erroneous belief that stalking is typically, if not only, perpetrated by individuals who are no longer in a relationship or have never been in a relationship, and that stalking-behaviors by a current partner may be viewed as only attempts to control ones partner. Although it is outside the scope of this paper to discuss the conceptual similarities and distinctions between stalking and controlling behaviors, we believe it is warranted to investigate stalking by a current dating partner, given the very high levels of dating violence evidenced in these relationships and some researchers' acknowledgment that this is an understudied and important topic (e.g., Davis et al 2012). It will also be important for research to examine whether stalking behaviors are associated with other forms of violence, including psychological and physical aggression.…”
Section: Stalking: Definitions and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Although these mechanisms are assumed to apply to men and women equally (e.g., Cupach & Spitzberg, 2004;Davis, Swan, & Gambone, 2012), it seems that they especially render women to perpetuate in their attempts to re-establish the broken relationship.…”
Section: Risk Factors Of Upbmentioning
confidence: 99%
“…Davis et al (2012), for instance, recently introduced a theory of coercive control that outlines gender differences in control motives underlying persistent pursuit.…”
Section: Implications Strengths and Limitationsmentioning
confidence: 99%